2017
DOI: 10.1080/13880209.2017.1296003
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition and anticancer activity in colon carcinoma cell lines of Prunus dulcis seed oil

Abstract: Context: Almond oil is used in traditional and complementary therapies for its numerous health benefits due to high unsaturated fatty acids content.Objectives: This study investigated the composition and in vitro anticancer activity of almond oil from Northern Cyprus and compared with almond oil from Turkey.Materials and methods: Almond oil from Northern Cyprus was obtained by supercritical CO2 extraction and analyzed by GC-MS. Almond oil of Turkey was provided from Turkish pharmacies. Different concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 36 publications
(32 reference statements)
0
35
0
4
Order By: Relevance
“…CPS oils were obtained by using supercritical CO2 extraction (Super critical fluid extraction 100-2-FMC system) (Thar Instruments Inc.) method. Fatty acid composition of spiny and thornless CPS oils were investigated by gas chromatography-mass spectrometry (GC-MS) analysis [3]. Colo-320 (ATCC catalogue: CCL 220) and Colo-741 cell lines (ECACC 93052621) are maintained in culture in RPMI-1640 medium (Biochrom, FG1215, Berlin, Germany), 10% FBS (Capricorn Scientific, FBS-11B, Ebsdorfergrund, Germany), 1% penicillin-streptomycin (Biochrom, A2213, Berlin, Germany) and 1% glutamine (EMD Millipore, K0282, Darmstadt, Germany) in a humidified atmosphere at 37 °C and 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…CPS oils were obtained by using supercritical CO2 extraction (Super critical fluid extraction 100-2-FMC system) (Thar Instruments Inc.) method. Fatty acid composition of spiny and thornless CPS oils were investigated by gas chromatography-mass spectrometry (GC-MS) analysis [3]. Colo-320 (ATCC catalogue: CCL 220) and Colo-741 cell lines (ECACC 93052621) are maintained in culture in RPMI-1640 medium (Biochrom, FG1215, Berlin, Germany), 10% FBS (Capricorn Scientific, FBS-11B, Ebsdorfergrund, Germany), 1% penicillin-streptomycin (Biochrom, A2213, Berlin, Germany) and 1% glutamine (EMD Millipore, K0282, Darmstadt, Germany) in a humidified atmosphere at 37 °C and 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacogenic and toxicity properties of all studied compounds also are computed and confirmed that most of all studied bioactive compounds especially, caulerpin obey Zaleya decandra [8] Ceramium virgatum [18] Ulva intestinalis [18] Fucus sp. [19] Chlorella vulgaris [20] Torreya Grandis [21] Hazelnut [22] Antimicrobial, [22] anticancer, [23] and antiviral activities [24] Saringosterols (2,3) Terrestrial plant Red macroalgae Green macroalgae Brown macroalgae…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid compounds in herbal plants have a role as chemopreventive agents or cause cell cycle inhibition and trigger apoptosis in cancer cells [41]. The results of this study revealed that a lower IC 50 value indicates a higher anticancer activity.…”
Section: Discussionmentioning
confidence: 67%